Pseudo-quantities, New Public Management and Human Judgement - Sven-Eric Liedman (Linköping University Electronic Press, 2012)
In this article I will introduce a new concept: pseudoquantities. A pseudo-quantity is a spurious quantity that purports to indicate the dimensions of something but is actually arbitrary and, if taken at face value, misleading. A real quantity informs us about the number, weight or velocity of something and is, in this respect, always more exact than even the most exhaustive verbal description. By contrast, a pseudo-quantity is less nuanced and less exact than a ellinformed and conscientious verbal evaluation. The term pseudo-quantity is new, but the phenomenon is well known to researchers and has become the subject of a rapidly growing stream of literature.1 The new term would primarily be intended to provide insight into the on-going mechanisms and processes that underlie this phenomenon. Furthermore, this term has a critical potential that is urgently needed at a time when many individuals erroneously believe that pseudoquantities can be used to gain both time and perspective. In the first part of the article, I will present the new concept and its background in the concepts of quality and quantity. The importance of this term is pertinent to the founding of New Public Management (NPM) in the public sector. NPM will be treated in the following section. I will specifically highlight how this process influences education and research. In the conclusion, I summarise my argument and provide insight regarding a possible alternative.